Clinical Significance of Neutrophil Adhesion Molecules Expression after Coronary Angioplasty on the Development of Restenosis - Inoue, Teruo; Sakai, Yoshihiko; Fujito, Tsuneo; Hoshi, Kazuhiro; Hayashi, Terumi; Takayanagi, Kan; Morooka, Shigenori (Thrombosis and Haemostasis, 1998)
To investigate the neutrophil activation process following percutaneous transluminal coronary angioplasty (PTCA), we examined the expressions of Mac-1 (CD11b/CD18), L-selectin (CD62L), and sialyl-LewisX (SLX) on the surface of neutrophils after the PTCA procedure, by flow cytometric analysis. Twenty-nine patients with single vessel coronary artery disease of the left anterior descending artery who underwent elective PTCA were enrolled. In the 17 patients without restenosis at the follow-up angiography, the mean channel fluorescence intensity (MFI) for CD18, CD62L and SLX did not change after PTCA. Only the CD11b level was increased at 48 h after the PTCA. In the remaining 12 patients who developed restenosis, the MFI values for CD18 and CD11b were increased at 24 h and 48 h after the PTCA. The MFI value for CD62L was decreased and that for SLX was increased at 48 h after the PTCA. These changes were more prominent in the coronary sinus blood samples than in those of the peripheral blood samples.Our data indicate the down-regulation of L-selectin, probably by shedding, as well as the up-regulations of Mac-1 and sialyl-LewisX, especially in patients with restenosis. It is suggested that neutrophil activation by an interaction between the selectin family and carbohydrate ligands after PTCA may play a role in the development of restenosis, as does the integrin family.